PENGARUH STRATEGI PEMBELAJARAN INKUIRI BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS ARGUMENTASI - Herboni, Yesi; Abdurahman, Abdurahman; Ratna, Ellya (Universitas Negeri Padang, 2016)
ABSTRACT This research aim at describing the effect of inquiry teaching and learning strategy using audiovisual toward student’s argumentative writing. Method used is experimental research. Based on the data analysis, it can be concluded that. First, student’s writing argumnetative skill at grade X SMA Negeri 1 Sungai Pua especially control class is moderate (66,91). Second, student’s writing argumentative skill at grade X SMA Negeri 1 Sungai Pua especially experimente class is good (81,94). Third, inquiry teaching and learning strategy inquiry audiovisual influential to ward student’s writing argumentative skill at grade X SMA Negeri 1 Sungai Pua because t counted is bigger than t table (7,28>1,698). Kata kunci: pengaruh, strategi pembelajaran inkuiri, argumentasi